2020
DOI: 10.1111/psyp.13656
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac defense reactivity and cognitive flexibility in high‐ and low‐resilience women

Abstract: Resilience is the process of adapting well in the face of adversity, trauma, tragedy, threats, or even significant sources of stress (American Psychological Association, 2014). Moreover, resilience involves the ability to recover and maintain adaptive behavior after stressful events. Psychophysiological and neuropsychological systems involved in the successful regulation and modification of emotions and cognitions are potential underpinnings of resilience. The parasympathetic nervous system facilitates adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…For example, Walker et al (2019) found a steeper decrease (compared with a 2 s pre-stimulus baseline) following acoustic startle stimuli among more compared to less resilient cohorts. Otero et al (2020) observed more resilient women displayed lower SCL than did less resilient women from nine to 70 s after exposure to white noise, though no resilience group difference was observed when the first nine seconds following exposure were included in analyses. Similarly, there was no SCL difference between HPR and LPR subgroups in this study immediately following shock, though over the five-minute general recovery period, SCL showed a significant decrease among HPR members compared to other subgroups.…”
Section: Discussionmentioning
confidence: 73%
“…For example, Walker et al (2019) found a steeper decrease (compared with a 2 s pre-stimulus baseline) following acoustic startle stimuli among more compared to less resilient cohorts. Otero et al (2020) observed more resilient women displayed lower SCL than did less resilient women from nine to 70 s after exposure to white noise, though no resilience group difference was observed when the first nine seconds following exposure were included in analyses. Similarly, there was no SCL difference between HPR and LPR subgroups in this study immediately following shock, though over the five-minute general recovery period, SCL showed a significant decrease among HPR members compared to other subgroups.…”
Section: Discussionmentioning
confidence: 73%
“…One such construct is cognitive flexibility , defined as the ability to adaptively switch cognitive sets to better suit the environment [ 32 ]. Multiple studies have found a significant positive correlation between cognitive flexibility and resilience [ 74 ] showing for example that more resilient individuals can flexibly apply different coping strategies depending on the circumstances, rather than being set in implementing only one strategy [ 93 ]. The construct of mindfulness , defined as the ability to intentionally focus attention on the present moment non-judgementally [ 46 ], has also been shown to be a significant predictor of resilience [ 44 , 48 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of these features is resilience, which plays a significant role in most psychological disorders ( 28 - 30 ) and is defined as individuals’ capacity to adjust efficiently, cope with, or overcome adversity or stress and potential disruptions ( 31 , 32 ). This protective factor makes a person more resilient against adverse events, leading to positive results ( 33 ). Resilience means that a person can effectively adjust to change, resist the negative effects of stressors, and avoid psychological disorders ( 33 , 37 ).…”
mentioning
confidence: 99%
“…This protective factor makes a person more resilient against adverse events, leading to positive results ( 33 ). Resilience means that a person can effectively adjust to change, resist the negative effects of stressors, and avoid psychological disorders ( 33 , 37 ). Earlier studies have reported that people with high levels of resilience show low levels of vulnerability and disease risk ( 33 , 37 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation